Assessing knowledge of primary school teachers on specific learning disabilities in two schools in India - Lingeswaran, Anand (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Evaluation of fund of knowledge about SLD among kindergarten and primary school teachers is essential to avoid misdiagnosis of SLD and to plan for specific teacher education to enable early identification of SLD among children. AIM: To assess the knowledge of learning disability among primary school teachers in India and to investigate its psychometric properties. MATERIALS AND METHODS: An observational study was carried out 34 primary school teachers from 2 different schools in Puducherry town agreed to participate in this study with informed consent. We used a multiple choice questionnaire format with a total of 50 questions, 5 choices for each question and a total score of 50. The study was held at the schools where these teachers were employed using pen and paper testing method and data were entered into the computer for statistical analysis. STATISTICAL ANALYSIS: Total scores on the questionnaire of all teachers were calculated. Content validity, reliability coefficient, discrimination factor, and facility factor were analyzed using SPSS software. RESULTS: 29% of the questions were correctly answered by all 34 teachers. The mean total score for this sample was 14.50 ± 9 and total item score for the 50 items was 9.90 ± 4. Cronbach's (α) reliability was 0.89. Overall discrimination index was + 0.2 and facility factor analysis score was 0.26. CONCLUSIONS: Validation of this new screening questionnaire was successful in Indian setting. It has to be used in other settings to extrapolate our findings.